2016
DOI: 10.3991/ijet.v11i04.5124
|View full text |Cite
|
Sign up to set email alerts
|

Revision Through Twitter: Do Tweets Affect Students’ Performance?

Abstract: Abstract-Twitter is one of the free micro bloggings available today. Created in 2006, Twitter has about 500 million registered users worldwide. Many scholars have been debating over the use of Twitter in teaching and learning. This brief research paper aims to look at Twitter as a source of revision for a course offered at the Defence University in Kuala Lumpur. The assumption is that the students are able to score a higher grade when Twitter is used as a revision tool. 32 students participated in this study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, Twitter also provides a convenient way to collaborate on assignments outside of class and to find intellectually stimulating interactions they would not have otherwise had (Gooding, Yinger, & Gregory, 2016;Hitchcock & Young, 2016;Juhary, 2016). According to Lin, Hoffman, & Borengasser, 2013, the collaboration among students only occurred when prompted by a professor or authoritative figure, while another study by Osatuyi and Passerini (2016) found the exact opposite to be true.…”
Section: Communication Affordancementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Twitter also provides a convenient way to collaborate on assignments outside of class and to find intellectually stimulating interactions they would not have otherwise had (Gooding, Yinger, & Gregory, 2016;Hitchcock & Young, 2016;Juhary, 2016). According to Lin, Hoffman, & Borengasser, 2013, the collaboration among students only occurred when prompted by a professor or authoritative figure, while another study by Osatuyi and Passerini (2016) found the exact opposite to be true.…”
Section: Communication Affordancementioning
confidence: 99%
“…For instance, respondents used the platform for advocacy, keeping up with current issues, professional information, news, and exposure to new ideas (Camiel, Goldman-Levine, Kostka-Rokosz, & McCloskey, 2014;Greenhalgh et al, 2016;Nicholson & Galguera, 2013;Rehm & Notten, 2016). In classes, it provided an online forum that made sharing resources and information far easier and was considered a useful tool, especially in obtaining supplemental material (Desselle, 2017;Juhary, 2016;Lin et al, 2013;Stephens & Gunther, 2016). This led to students demonstrating improvement in classes with Twitter use than those without it (Fewell, 2014).…”
Section: Information Sharingmentioning
confidence: 99%
“…Furthermore, the SPOC-based flipped classroom of college English also utilizes such social interaction platforms as Microblog, [12] Twitter, [13] Wechat and QQ to introduce students' works in learning, which further help students to acquire positive emotions by gaining a sense of achievement in English learning.…”
Section: Spoc-based Flipped Classroom Of College English: Its Supportmentioning
confidence: 99%
“…In this sense, organizing knowledge into OAV triplets makes THOTH suitable for microlearning. In Juhary [21], Twitter was explored as a revision tool, well accepted by students. His research led to conclude that students performed better in their tests after using Twitter in revision activities.…”
Section: Thoth and Microlearningmentioning
confidence: 99%